Lysyl oxidases: linking structures and immunity in the tumor microenvironment - Tenti, Paolo; Vannucci, Luca (Cancer immunology and immunotherapy, 2020)
The lysyl oxidases (LOXs) are a family of enzymes deputed to cross-link collagen and elastin, shaping the structure and strength of the extracellular matrix (ECM). However, many novel "non-canonical" functions, alternative substrates, and regulatory mechanisms have been described and are being continuously elucidated. The activity of LOXs, therefore, appears to be integrated into a complex network of signals regulating many cell functions, including survival/proliferation/differentiation. Among these signaling pathways, TGF-β and PI3K/Akt/mTOR, in particular, cross-talk extensively with each other and with LOXs also initiating complex feedback loops which modulate the activity of LOXs and direct the remodeling of the ECM. A growing body of evidence indicates that LOXs are not only important in the homeostasis of the normal structure of the ECM, but are also implicated in the establishment and maturation of the tumor microenvironment. LOXs' association with advanced and metastatic cancer is well established; however, there is enough evidence to support a significant role of LOXs in the transformation of normal epithelial cells, in the accelerated tumor development and the induction of invasion of the premalignant epithelium. A better understanding of LOXs and their interactions with the different elements of the tumor immune microenvironment will prove invaluable in the design of novel anti-tumor strategies.
Keywords: regulace genové exprese u nádorů; Animals; biologické markery; Protein-Lysine 6-Oxidase; Biomarkers; multigenová rodina; Gene Expression Regulation, Neoplastic; Neoplasms; nádory; nádorové mikroprostředí; Structure-Activity Relationship; lidé; Immunity; signální transdukce; Signal Transduction; extracelulární matrix; imunita; Humans; lysyloxidasa; Extracellular Matrix; vztahy mezi strukturou a aktivitou; Tumor Microenvironment; zvířata; Multigene Family